Role of TFH Cells in Promoting T Helper 17-Induced Neuroinflammation - Quinn, James L.; Kumar, Gaurav; Agasing, Agnieshka; Ko, Rose M.; Axtell, Robert C. (Frontiers in Immunology, 2018)
Both T cells and B cells are implicated in the pathology of multiple sclerosis (MS), but how these cells cooperate to drive disease remains unclear. Recent studies using experimental autoimmune encephalomyelitis (EAE) demonstrated that the TH17 pathway is correlated with increased numbers of ectopic B-cell follicles in the CNS. As follicular T helper (TFH) cells are regulators of B cell responses, we sought to examine the role of TFH cells in EAE induced by the transfer of myelin-specific TH17 cells (TH17-EAE). In this study, we first confirmed previous reports that B-cells are a major cell type infiltrating the CNS during TH17-EAE. In addition, we found that B cells contribute to the severity of TH17-EAE. Class-switched B-cells in the CNS were positively correlated with disease and, strikingly, the severity TH17-EAE was diminished in B cell deficient mice. We next focused on the role TFH cells play in TH17-EAE. We found substantial numbers of CXCR5+PD1+CD4+ TFH cells in the CNS tissue of TH17-EAE mice and that at the peak of disease, the number of infiltrating TFHs was correlated with the number of infiltrating B-cells. Using congenic CD45.1+ donor mice and CD45.2+ recipient mice, we determined that the TFH cells were recipient-derived, whereas IL-17+ cells were donor-derived. We assessed whether myelin-specific TFH cells are capable of inducing EAE in recipient mice and found that transferring TFH cells failed to induce EAE. Finally, we tested the effects of blocking TFH trafficking in TH17-EAE using an antagonistic antibody against CXCL13, the chemokine ligand for CXCR5 on TFH cells. We found anti-CXCL13 treatment significantly reduced TH17-EAE disease. This treatment blocked CD4+ T cells from entering the CNS, but had no effect on infiltration of B cells. Strikingly, this antibody treatment had no measurable effect on TH17 disease in B cell-deficient mice. These data demonstrate that infiltrating TFH cells are a key cell type that contributes to an inflammatory B cell response in TH17-EAE and provide evidence for targeting TFH cells as a treatment for neuro-autoimmune diseases like MS.